Beliefs, Practices, and Personalities of Software Engineers: A Survey in a Large Software Company - Smith, Edward K.; Bird, Christian; Zimmermann, Tom (Proceedings of the 9th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE 2016), 2016)
In this paper we present the results from a survey about the beliefs, practices, and personalities of software engineers in a large software company. The survey received 797 responses. We report statistics about beliefs of software engineers, their work practices, as well as differences in those with respect to personality traits. For example, we observed no personality differences between developers and testers; managers were conscientious and more extraverted. We observed several differences for engineers who are listening to music and for engineers who have built a tool. We also observed that engineers who agree with the statement “Agile development is awesome” were more extroverted and less neurotic.